Influence of Nonopioid Analgesics on Healthy Nucleus Pulposus Cells. (May 2014) - Eder, C.; Trifinopoulos, J.; Schildboeck, S.; Koppensteiner, N.; Zolles, J.; Falkner, E.; Ogon, M.
Introduction: Recent advances in our understanding of intervertebral disc biology led to an increased interest in the development of cell transplantation therapies. To allow percutaneous, fluoroscopically guided cell transplantation, single cells suspended in a fluid or hydrogel carrier are usually applied. As the physiological situation of the nucleus pulposus cell is the solid tissue compound, single cells lacking their specific extracellular environment might be more sensitive to pharmacological noxa. The aim of the present study is to test the effect of three different nonopioid analgesics on proliferation, viability, and differentiation features of healthy nucleus pulposus cells. Materials and Methods: Bovine nucleus pulposus cell cultures were generated from cadaver material. Cells were plated at a density of 5 × 10 4 cells per well into 24 well plates and incubated with Dulbecco's Modified Eagle's Medium (DMEM) supplemented with 10% Fetal Calf Serum (FCS), 0.05 mg/mL Ascorbic Acid and 2 mM L-Glutamine (control group) or in medium additionally supplemented with either 2.6 µg/mL Diclofenac-Natrium (Diclobene), 60 µg/mL Metamizole-Natrium (Novalgin) or 30 µg/mL Paracetamol (Perfalgan). Dosage was chosen according to plasma levels after intravenous administration. Cell proliferation and viability were assessed over 5 days and reassessed after cessation of drug supplementation. Collagen and Glycosaminoglycan synthesis were evaluated from 3-d-pellet cultures. All experiments were performed in triplicates and repeated on two different occasions. Experiments were repeated with a human cell line to test the conformity with the clinical situation. Results: Cell count after 24 hours was 6.7 × 10 4 in the control group, but only 4.2 × 10 4 (Metamizole) resp. 4.3 × 10 4 (Paracetamol) resp. 4.8 × 10 4 (Diclofenac); p < 0.0004 After 5 days of cell culture, cell counts increased to 84.2 × 10 4 in the control group, but only 69.1 × 10 4 after Diclofenac resp. 62.9 × 10 4 after paracetamol supplementation. Following supplementation with metamizole, cell counts increased to only 8 × 10 4 ( p < 0.0001). Human degenerative nucleus pulposus cells showed a comparable reaction to the test medication. After cessation of medication contact, cells originally cultured in medium supplemented with paracetamol or diclofenac needed more than 4 weeks to reach proliferation results comparable to control. Cells cultured in medium supplemented with metamizole showed no recovery at all and could not be expanded in vitro any more. Cell viability after 5 days of medication supplementation was 99% in the control group after diclofenac supplementation, 97% after paracetamol supplementation (n.s.) but only 74% after supplementation with metamizole ( p > 0.0001). Despite the poor performance of the metamizole-treated cells under monolayer conditions, no significant difference pellet size, glycosaminoglycan, or collagen synthesis were detected. The only noticeable difference to the other medication groups was irregular glycosaminoglycan staining and the prevalence of irregularly shaped cell nuclei. Conclusion: Nonopioid analgesics are a common component of pain therapy for degenerative disc disease. All three medications tested showed a significant decrease in cell proliferation. Metamizole showed the highest decrease in cell proliferation and viability and led to a reproducible dieback of nucleus pulposus cells during in vitro culture. We would therefore recommend not to use metamizole in patients planned for an intervertebral disc cell transplantation. Disclosure of Interest None declared